Analisis Pengelolaan Persediaan Dan Pertumbuhan Penjualan Terhadap Kesehatan Likuiditas Perusahaan - Puspitasari, Ratih; Sopiana, Eka (Jurnal Ilmiah Manajemen Kesatuan, 2015)
Inventory is an important element in a company asset. Due to various consideration such as decreasing factor, losses, and market changes of demands, the management has to constantly do a reviews supervisions so that the funds invested to the inventory will not overly spent and so the company's operational run as it should. The vain surplus of inventory will not only weakened the liquidity health ofa company but also could be a loss and otherpotential disadvantages. Management of inventory and product takes important part of company's operational continuity. Thus, wellorganized inventory management system is stmngly advised to ensure the wellness of the company's performance. To measure the company's performance in managing the inventory, the company can use analytic ratio that includes INTO (Inventory Turnover). One of other option is using company liquidity's health analysis to see if the inventory management and sales growth affects the health of company's liquidity. The purpose of this research is to identifi and analyze the ratio of inventory management, sales growth and the health of company's liquidity with the use of INTO ratio and the sales that measured with the current ratio. This research is based on PT. Mayora Indah, Tbk, PT. Indofood Sukses Makmur, Tbk. and PT.Ultrajaya Industry & Trading Company, that market in the Food & Beverages industrialfield. This research which used analytic ratio has proven that inventory management and a positive sales growth do not give any significant influence towards company's liquidity health, because the increasing or the decreasing of inventory management and sales growth are not always followed by the increasing or the decreasing ofthe health of company's liquidity. Keyword: Inventory Management, Sales Growt, Liquidity